Perencanaan Perawatan Mesin Nail Making Machine Untuk Meminimasi Adanya Downtime di CV. XYZ - Laksono, Dwi; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
CV. XYZ is a manufacturing company that produces nails and barbed wire. Thedestruction of nail making machines or (nail making machines), resulting in clock stops (downtime and delay) in the production process which results in machine performance becoming less effective and efficient. Effectiveness in the production process needs to be supported by maintenance and maintenance management on the machine for that effective steps are needed in machine maintenance to be able to overcome and prevent these problems.  This study conducted a literature study using books on Care Management, RCM Method, FMEA Method, LTA Method, and journals related to care management and also RCM Method. Maintenance intervals of critical components or components damaged 6 times a year with a maintenance time interval of 281 hours. While the side shaft components are damaged 4 times in one year with a maintenance time interval of 282 hours. Maintenance activities that need to be carried out to reduce failures in crank shaft components with the type of damage to the exhausted bearing lubricant need to be carried out schedule restoration task maintenance, the type of loose bearing damage needs to be carried out schedule discard task maintenance, and the type of loose or broken arm connection damage needs to be done schedule discard task. In side shaft components with broken types of metal handlebar connection damage, it is necessary to carry out schedule discard task maintenance, for damage to worn wire feeder loads, it is necessary to carry out schedule restoration task maintenance, and for loose metal wing damage, schedule restoration task activities need to be carried out.